In Search of the Smoking Gun: Linking Environmental Contamination to its Source - Gagnon, Monique; Scarlett, Alan G; Spilsbury, Francis D (SETAC Press, 2023)
Contamination of the environment may cause environmental and social issues that need to be rectified and are often costly. Under the ‘polluter pays’ principle, identifying the source of the contamination is a critical first step from a legal perspective. Similarly, in order to prevent further contamination, the source must first be correctly identified. To achieve this, some form of forensic ‘fingerprinting’ is required. Multiple techniques may be required to build a ‘weight of evidence’ to identify the source.